Chelator free gallium-68 radiolabelling of silica coated iron oxide nanorods via surface interactions. Issue 36 (20th August 2015) - Burke, Benjamin P.; Baghdadi, Neazar; Kownacka, Alicja E.; Nigam, Shubhanchi; Clemente, Gonçalo S.; Al-Yassiry, Mustafa M.; Domarkas, Juozas; Lorch, Mark; Pickles, Martin; Gibbs, Peter; Tripier, Raphaël; Cawthorne, Christopher; et al.
Abstract : Silica coated iron oxide nanorods can be radiolabelled with gallium-68 without the need for a chelator to give in vivo stable multimodal PET/MR imaging agents. Abstract : The commercial availability of combined magnetic resonance imaging (MRI)/positron emission tomography (PET) scanners for clinical use has increased demand for easily prepared agents which offer signal or contrast in both modalities. Herein we describe a new class of silica coated iron–oxide nanorods (NRs) coated with polyethylene glycol (PEG) and/or a tetraazamacrocyclic chelator (DO3A). Studies of the coated NRs validate their composition and confirm their properties as in vivo T 2 MRI contrast agents. Radiolabelling studies with the positron emitting radioisotope gallium-68 ( t 1/2 = 68 min) demonstrate that, in the presence of the silica coating, the macrocyclic chelator was not required for preparation of highly stable radiometal-NR constructs. In vivo PET-CT and MR imaging studies show the expected high liver uptake of gallium-68 radiolabelled nanorods with no significant release of gallium-68 metal ions, validating our innovation to provide a novel simple method for labelling of iron oxide NRs with a radiometal in the absence of a chelating unit that can be used for high sensitivity liver imaging.